Stress and Alterations in Bones: An Interdisciplinary Perspective - Wippert, Pia-Maria; Rector, Michael; Kuhn, Gisela; Wuertz-Kozak, Karin (Frontiers in Endocrinology, 2017)
Decades of research have demonstrated that physical stress stimulates bone remodeling and affects bone structure and function through complex mechanotransduction mechanisms. Re-cent research has laid ground to the hypothesis that mental stress also influences bone biology, eventually leading to osteoporosis and increased bone fracture risk. These effects are likely exerted by modulation of hypothalamic-pituitary-adrenal axis activity, resulting in an altered release of growth hormones, glucocorticoids and cytokines, as demonstrated in human and animal studies. Furthermore, molecular crosstalk between mental and physical stress is thought to exist, with either synergistic or preventative effects on bone disease progression depending on the characteristics of the applied stressor. This mini review will explain the emerging con-cept of mental stress as an important player in bone adaptation and its potential crosstalk with physical stress by summarizing the current state of knowledge, highlighting newly evolving notions (such as intergenerational transmission of stress and its epigenetic modifications af-fecting bone) and proposing new research directions.